Estimating soil erosion in urban areas by changes in soil properties (Mongolian Journal of Geography and Geoecology, 2023)
Soil erosion is mainly caused by anthropogenic activities and has been intensified in urban areas, where there are high population densities, industries, and constructions. In this study, we aimed to assess soil erosion in urban areas by examining changes in organic content, texture, and pH values of the soil. We collected soil samples from ten settlements of Bayankhongor Province and used a weather station site with fences as a control site. The findings revealed that there are substantial variations in the organic content of the soil. In comparison with the control site, organic content decreased and it was 10.6% in the provincial center, Bayankhongor, and